Innovation as Capability and Freedom: Charting a Course of TRIPS Patent Protection in a Fair and Balanced Global Innovation System - Yu, Sa (Université d'Ottawa / University of Ottawa, 2013)
This research aims to substantiate the idea that innovation is a capability that can be cultivated for equitable development and that a user’s freedom to innovate should not be violated by excessive intellectual property rights. The central feature of this idea is the principle of substantive equality of innovation capability, which is comprised of five components: equality of innovation opportunity, neutrality of innovation models, accessibility of the innovation commons, dignity of the entrepreneurial spirit, and respect for indigenous innovation. These five components will ensure that everyone has the basic innovation capability to function in the knowledge society and a real opportunity to access the innovation commons, mix her intellect with raw innovation resources, and participate in the decision-making process that affects her innovation capability and freedom. This thesis envisions a fair and balanced global innovation system and proposes a two-pronged approach to incorporate the TRIPS patent regime into this system. To promote multi-dimensional and equitable development, an innovation capability approach to development aims to maximize the contribution of intellectual resources to economic growth and human development through cultivating innovation capability and harnessing the power of non-proprietary innovation models. To increase the effectiveness of innovation systems and promote democratic innovation governance, an innovation equality and freedom approach to the TRIPS patent regime advances distributive justice and intergenerational equality objectives of the global innovation regime. A fair and balanced global innovation system has legal implications for both national governments and international institutions. A national government has the obligation to bring each and every citizen to a point of fair competition in the innovation market. This means that the government should provide equal opportunity to freely access the innovation commons and equally participate in the decision-making process that affects each person’s innovation capability and freedom. In addition, an optimal system of innovation ought to be based on a complementary combination of proprietary and non-proprietary systems in order to produce the highest attainable rates of innovation, productivity, and social utility. For international institutions, I suggest that the WIPO may be a more appropriate forum than the WTO for global innovation governance.
Keywords: TRIPS Agreement; Patent; Innovation; Development